(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
Background: Post-implant infections and peri-implant mucositis are common complications that can compromise the success of dental implants. Conventional mechanical and chemical decontamination methods often fail to completely eradicate bacterial biofilms. Photodynamic therapy (PDT) has emerged as a promising adjunctive technique that uses a photosensitizer and light energy to generate reactive oxygen species capable of destroying microorganisms. Methods: The study involved 40 patients (22 males, 18 females; aged 25–60 years) who underwent dental implantation. Twenty patients received standard post-implant care (control group), and twenty received additional PDT treatment (test group) using methylene blue (0.01%) activated by a diode laser (660 nm, 100 mW, 90 s per site). Clinical parameters, including probing depth (PD), bleeding on probing (BOP), and bacterial load, were recorded at baseline, 2 weeks, and 8 weeks post-treatment. Results: PDT significantly reduced peri-implant inflammation and bacterial counts compared to standard therapy. Mean PD decreased from 4.2 ± 0.8 mm to 2.6 ± 0.5 mm, and BOP incidence fell from 65% to 20% at 8 weeks. Microbial analysis revealed a 92% reduction in Porphyromonas gingivalis levels. Conclusion: Photodynamic therapy enhances soft tissue healing and bacterial reduction after implantation. It is a safe, non-invasive adjunctive method for managing peri-implant soft tissue complications and improving long-term implant success.